Strategi Komunikasi Transedental pada ODGJ di Yayasan Mentari Hati Tasikmalaya - Shilah Suci Anugerah (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2018)
The purpose of this study was to determine the process of implementing the communication carried out by Mr. Dadang in building the mentality of patients at the Mentari Hati Foundation in Tasikmalaya. To find out also the benefits felt by the ODGJ after receiving spiritual motivation. This Research One type of descriptive qualitative research is in the form of research with a case study method or approach (Case Study). This research focuses intensively on one particular object which is studied as a case. Meanwhile, in terms of approach, this theory uses a qualitative approach. This research method is not to test hypotheses, but to provide a thorough and in-depth explanation of the research results. This research belongs to the type of qualitative research, in which data and findings are presented in the form of a description or description of words, not tested or analyzed with statistical or mathematical numbers. The transcendental communication strategy carried out by Mr. Dadang includes aspects of dhikr meditation, shalawat reading, and recitation of the holy Qur'an.